2011
DOI: 10.1002/j.0022-0337.2011.75.11.tb05199.x
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative HIV Training Program for Dental Students

Abstract: Dentists need to be able to give people with HIV/AIDS compassionate and comprehensive care. Previous studies have shown that many dental students have negative attitudes towards treating such individuals. This article addresses the effectiveness of a program that trains dental students in the issues of treating this population. All predoctoral students at the Loma Linda University School of Dentistry are required to receive this training. Students complete a pre-session survey during their third year and a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…Similar results were found by Rogers et al which indicated an increase in comfort and attitude among dental students working with PLWH after specialized training for working with PLWH. [37] While the literature indicates the presence of behaviors such as those measured by HAPSI, [2,3] the current sample revealed no such trend. The majority of the literature focused on the presence of these behaviors in clinicians has been conducted in the developing world.…”
Section: Discussioncontrasting
confidence: 55%
“…Similar results were found by Rogers et al which indicated an increase in comfort and attitude among dental students working with PLWH after specialized training for working with PLWH. [37] While the literature indicates the presence of behaviors such as those measured by HAPSI, [2,3] the current sample revealed no such trend. The majority of the literature focused on the presence of these behaviors in clinicians has been conducted in the developing world.…”
Section: Discussioncontrasting
confidence: 55%
“…Training programs for dentists and dental students have been implemented to include evidence‐based techniques in such areas as motivational interviewing, smoking cessation counseling, dental treatment of HIV+ patients and early detection of child abuse and neglect. These have been accompanied by documented changes in dentists’ confidence, behaviors and practices . Within the medical community, brief training for medical residents in the management of substance misuse has shown improvements in substance misuse inquiry, due notably to increased provider confidence and treatment optimism .…”
Section: Discussionmentioning
confidence: 99%
“…Surveys were distributed and students evaluated their knowledge and attitudes in applying infection control and postexposure prophylaxis following any exposure to the virus. After the programme concluded, there was a significant increase in the students' knowledge of and attitudes towards patients with HIV/AIDS. This demonstrates that an intervention can yield positive results regarding the course of action that should be taken should transmission of the virus occur.…”
Section: Discussionmentioning
confidence: 87%